Applying market basket analysis to official statistical data - Szymkowiak, Marcin; Klimanek, Tomasz; Józefowski, Tomasz (Analiza koszykowa i jejzastosowania w statystyce publicznej, 2018)
Market basket analysis, which is a method of discovering co-occurrence relationships, is widely used for the purposes of marketing research and e-commerce, mainly by supermarkets and online stores. Moving beyond the traditional notion of a market basket understood as a fixed list of products, the technique can be applied for data mining in other fields of research which do not involve traditional transactions and purchases made by customers. The following article describes theoretical aspects of market basket analysis with an illustrative application based on data from the National Census of Population and Housing 2011 with respect to marital status. This is the first application of market basket analysis to census data to be conducted in Poland, in which attributes of the market basket have been replaced with respondents’ demographic characteristics. This approach makes it possible to identify relationships between legal (de jure) marital status and actual (de facto) marital status, taking into account other basic socio-demographic variables available in large datasets. Using the R software to generate choropleth maps classified by province as a method of visualizing association rules, it was possible to conduct a spatial analysis of the phenomenon of interest
Econometrics = Ekonometria, 2018, Vol. 22, No. 1, s. 39-57
Keywords: market basket analysis; Apriori algorithm; National Census of Population and Housing 2011; marital status; arules package; arulesViz package; analiza koszykowa; algorytm Apriori; Narodowy Spis Powszechny Ludności i Mieszkań 2011; stan cywilny; pakiet arules; pakiet arulesViz